Origin, age and petrogenesis of barren (low-grade) granitoids from the Bezenjan-Bardsir magmatic complex, southeast of the Urumieh-Dokhtar magmatic belt, Iran - Sepidbar, F; Ao, S; Palin, R; Li, Q; Zhang, Z (Elsevier, 2018)
The Bezenjan-Bardsir magmatic complex (BBMC), situated at the southeastern part of the Urumieh-Dokhtar magmatic belt, includes a thick pile of volcanic rocks intruded by younger granitoids. The granitoids have granodioritic to quartz-monzonitic composition, while volcanic rocks are petrologically classified as basaltic andesite, andesite, dacite, rhyodacite, and rhyolite. In this study, U–Pb zircon geochronology, whole-rock geochemistry, and Sr–Nd isotopic analyses were performed on a wide range of granitoids exposed within the BBMC. This geochronology indicates that barren magmatism occurred during the Middle to Late Oligocene (29–23 Ma), followed by large-scale Cu mineralization during the Late Miocene. These BBMC rocks have strong depletions in Nb (2.5–17.3 ppm) and enrichments in light rare earth elements and large ion lithophile elements compared to N-MORB. Their normal calc-alkaline arc geochemical signature (low Sr/Y ratio of almost <55), negative Eu anomalies (Eu/Eu∗ = 0.6–1), enrichment in HFSE and the negative to positive εNd (t) values of −1.23 to +3.17, the Nd model ages (0.43–0.72 Ga) and radiogenic Sr isotope signatures (87Sr/86Sr = 0.7048–0.7063) suggest generation in a subduction zone setting; however, productive rocks elsewhere within the UDMB exhibit adakite-like calc-alkaline magmatic characteristics (high Sr and Sr/Y, but low Y). The BBMC igneous rocks show low Sr/Y (14.6–45.2), zircon Ce(IV)/Ce(III) (12–703), and Eu/Eu∗ (0.08–0.64) ratios, negative to slightly positive Eu anomalies, and enrichment in HFSE and 87Sr/86Sr, in agreement with other barren-type magmas through the UDMB. An integrated geochemical, petrological, and tectonic model suggests that barren magmatism in the BBMC was likely associated with partial melting of juvenile lower crust (amphibolite) due to northwestward subduction of the Neo-Tethys oceanic lithosphere, whereas productive adakitic rocks within the UDMB formed by partial melting of thickened lower crust (garnet-amphibolite).